Controller gain tuning for road vehicle following in a convoy system - Uthman Hassan, Aveen (2014)
Recently, vehicle convoy system has been one of the interesting topics to researchers, since it has the ability to perform tasks more powerfully than individual vehicles. Control strategy issue in this system also needs to be considered and analysed. In a convoy system, the control system on the following vehicle requires information about preceding vehicle motion, in order to maintain stability and satisfy operating constraints. A two-vehicle look-ahead control strategy is proposed and investigated for the operation of a convoy. Firstly, the mathematical modeling for this control strategy is done and later it is simulated to ensure the following stability of the operation. This research also includes design and simulation of an adaptive gain controller for road vehicle following in convoy system (including three vehicles). The control strategy is designed such that the controller gain is adaptively adjusted. Model Reference Adaptive Control (MRAC) design, gradient approach and Lyapunov approach are applied in the tuning of gains in the system. The appropriate constants are used as the reference model for the adaptive controller implementation to find the effectiveness of the control. As a result, a road vehicle following in convoy system with an adaptive gain controller is produced Description